Panel Analyzes Pakistan's Internal Water Concerns. (11th June 2013) - Showstack, Randy
Abstract: Although transboundary water issues between Pakistan and neighboring countries may be exciting and interesting, Pakistan's real water and security nexus is at the local level, according to Daanish Mustafa, coauthor of a new report, "Understanding Pakistan's Water‐Security Nexus." Mustafa, a reader in politics and environment at King's College, London, U.K., was a panelist at a 30 May forum in Washington, D. C., sponsored by the United States Institute of Peace, which published the report.